Factors Affecting Working Performance Among Room Attendants at Sogo Hotel Novaliches Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Room attendants are responsible for maintaining rooms tidy and friendly. However, overworkcan lead to stress, exhaustion, body aches, and sickness. This can have an adverse effect onemployee performance, making it harder to accomplish goals. The purpose of this study is todetermine the factors affecting working performance among room attendants at SOGONovaliches Quezon City in terms of company culture, employee engagement, job satisfaction,and training and development.The result of this study reveals that among room attendants at sogo hotel experience, thefactors affecting working performance are evaluated as “Affected” in terms of companyculture, employee engagement, job satisfaction, and training and development; the problemencountered by the room attendant in terms of guest relation, diversity of guest, handling theguest request, communication skills, and supplies and materials are also affected the workingperformance of room attendant. The possible solution and strategy for a room attendant tocope with daily tasks to maintain good working performance in the housekeeping departmentand how the way the findings can be utilized in crafting a guide for factors affecting workingperformance among room attendants are also evaluated as “affected.” This will help topractice and improve the performance of room attendants to cope with the task.This study recommended that room attendant must improve their working performance andcope with the factors that affect performance, such as company culture, employeeengagement, job satisfaction, and training and development. It is a must to encourage andpromote the employee to have a good working performance.
Keywords: Hospitality Management